Hydroxychloroquine – Beyond Malaria: Its Role in Rheumatology and COVID-19 – A Literature Review - Ząbek, Adam Jan; Kuźniar, Jakub Paweł; Chrzanowska, Emilia Gabriela; Zagalska, Michalina; Turek, Marta; Tamborski, Tomasz; Grzebinoga, Adam; Szlążek, Julia; Pudełko, Iwona; Roguska , Barbara (Journal of Education, Health and Sport, 2025)
Hydroxychloroquine (HCQ) is a long-established drug, initially used to treat malaria and later widely applied in autoimmune diseases such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). As an immunomodulatory agent, HCQ plays a crucial role in managing chronic inflammation. Despite its benefits, its use requires monitoring due to potential adverse effects, including retinopathy and myopathy.[1] Objective This review analyzes HCQ’s role in modern medicine and public health, particularly in treating autoimmune diseases. It also examines controversies surrounding its use during the COVID-19 pandemic and its implications for medical education and health prevention. Current Knowledge HCQ modulates immune responses and lysosomal function, making it effective in controlling inflammation. Although hypotheses suggested antiviral properties against SARS-CoV-2, clinical trials did not confirm its efficacy, leading to changes in treatment recommendations. Methods A literature review of 32 scientific articles was conducted using PubMed and Google Scholar, focusing on HCQ’s history, mechanism of action, and applications in medicine, public health, and education. Conclusion HCQ remains a key treatment for autoimmune diseases, though its long-term safety is still under study. Continuous research and medical education are essential for optimizing its use, including potential applications in sports and rehabilitation, where chronic inflammation affects recovery and performance.